Tajwid Warna dalam Mushaf Al-Qur'an Standar Indonesia - Harits Fadlly (SUHUF, 2020)
After the stipulation of the Indonesian Standard Mushaf in 1984, the publication of the Mushaf in Indonesia began to appear to develop. One proof of this development is the emergence of the color tajweed mushaf. In general, this paper discusses the use of the color tajweed system in the Mushaf, either before or after the publication of the Color System Tajweed Guidelines in 2011. This paper uses a qualitative method with a sociological-historical approach to examine historical aspects, genealogy, and the function of color tajweed. Data collection was carried out by means of inventory, documentation, literature study, and in-depth interviews with publishers and users of the color tajweed mushaf. Color tajweed mushaf appeared in Indonesia in 2005. In the beginning, publishers printed the Mushaf with different tajweed colors from one publisher to another, causing confusion in the community. After the publication of the Color System Tajweed Guidelines, the publication of the color tajweed mushaf was more regular. In terms of sales from 2005 to 2020, there is a significant increase. One of the contributing factors is the increasing segment of middle Muslim society in Indonesia. Keywords: Color Tajweed, Indonesian Standard Mushaf, Tajweed Guidelines.